The Use of Participatory and Non-Experimental Research Methods in Behavior Analysis - Guerin, Bernard (Perspectivas em Análise do Comportamento, 2019)
This paper seeks to enlarge the range of research methods in behavior analysis to deal with situations in which even small- or single-sample experimental methods are not possible or not appropriate. This is common for most research with humans, and especially with behaviors under the rubric of social, cultural and verbal. After presenting arguments for this, the paper outlines three methods for describing the everyday, complex structuring of functional relations. The most important of these methods adapts engaged, participatory methods from other social sciences but puts the focus on finding functional relations between behaviors and their complex outcomes rather than just labelling the hidden functional relations as static social ‘structures’. Examples of these three methods are given from research on functional analyses of mental health behaviors.